Computer-Aided Design of Antimicrobial Peptides: Are We Generating Effective Drug Candidates? - Cardoso, Marlon H.; Orozco, Raquel Q.; Rezende, Samilla B.; Rodrigues, Gisele; Oshiro, Karen G. N.; Cândido, Elizabete S.; Franco, Octávio L. (Frontiers in Microbiology, 2020)
Antimicrobial peptides (AMPs), especially antibacterial peptides, have been widely investigated as potential alternatives to antibiotic-based therapies. Indeed, naturally occurring and synthetic AMPs have shown promising results against a series of clinically relevant bacteria. Even so, this class of antimicrobials has continuously failed clinical trials at some point, highlighting the importance of AMP optimization. In this context, the computer-aided design of AMPs has put together crucial information on chemical parameters and bioactivities in AMP sequences, thus providing modes of prediction to evaluate the antibacterial potential of a candidate sequence before synthesis. Quantitative structure-activity relationship (QSAR) computational models, for instance, have greatly contributed to AMP sequence optimization aiming at improved biological activities. Besides machine-learning methods, mainly artificial neural networks, along with sophisticated models for stochastic optimization have shown the potential to boost the automated design of AMPs. However, how successful have these approaches been in generating effective antibacterial drug candidates? Bearing this in mind, this review will focus on the main computational strategies that have generated AMPs with promising activities against pathogenic bacteria, as well as anti-infective potential in different animal models, including sepsis and cutaneous infections. Moreover, we will point out recent studies on the computer-aided design of antibiofilm peptides. As expected from automated design strategies, diverse candidate sequences with different structural arrangements have been generated and deposited in databases. We will therefore also discuss the structural diversity that has been engendered.